2012
DOI: 10.1590/s0102-36162012000500019
|View full text |Cite
|
Sign up to set email alerts
|

Osteoma osteoide em escafoide: relato de caso

Abstract: Osteoid osteoma is a benign osteoblastic tumor that is unusual in the hand. A location in the carpal bones is infrequent, which leads to errors in diagnosing it because of polymorphism of the clinical symptoms. Reviewing the literature shows that nine cases of osteoid osteoma in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
1
0
2
Order By: Relevance
“…9 Pohlenz et al 10 suggest that the success rate is due to experience and postoperative support in a high-volume hospital. In our study, as well as in the literature, 11 12 13 we observed an increased incidence of male young patients with traumatic injuries, especially due to traffic accidents (53% of the cases). In these cases, it is important to perform a combined treatment with bone stabilization or reconstruction with skin coverage, with simultaneous teams.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…9 Pohlenz et al 10 suggest that the success rate is due to experience and postoperative support in a high-volume hospital. In our study, as well as in the literature, 11 12 13 we observed an increased incidence of male young patients with traumatic injuries, especially due to traffic accidents (53% of the cases). In these cases, it is important to perform a combined treatment with bone stabilization or reconstruction with skin coverage, with simultaneous teams.…”
Section: Discussionsupporting
confidence: 81%
“…9 Pohlenz et al 10 citaram que a taxa de êxito cirúrgico em um grande centro hospitalar se deve à experiência e ao suporte pós-operatório. Em nosso estudo, assim como na literatura, 11 12 13 observamos um aumento da incidência de pacientes jovens do sexo masculino com lesões traumáticas, principalmente por acidentes de trânsito (53% dos casos). Nestes casos, é importante realizar um tratamento combinado, com estabilização óssea, reconstrução com cobertura cutânea, e com diversas equipes especializadas, tudo com o objetivo de reduzir o número de cirurgias, as taxas de infecção e o tempo de hospitalização, 14 É importante que sejam instalados centros de microcirurgia reconstrutiva nos hospitais ortopédicos.…”
Section: Discussionunclassified
“…1 2 Esta doença foi inicialmente descrita como uma compressão causada por uma fratura distal do rádio por Paget em 1854. 3 4 5 O nervo mediano progride para o nível do punho adjacente a nove tendões no túnel do carpo, um canal osteofibroso inextensível. Os pacientes queixam-se de dor e parestesia com piora à noite.…”
Section: Introductionunclassified
“…1 2 This pathology was initially described by compression caused by a distal radius fracture by Paget in 1854. 3 4 5 The median nerve progresses to the wrist level adjacent to nine tendons in the carpal tunnel, an inextensible osteofibrous canal. Patients complain of pain and paresthesia, worst at night.…”
Section: Introductionmentioning
confidence: 99%